ZIF-L-derived alkaline electrolytic water oxygen evolution catalyst as well as preparation method and application thereof

By using ZIF-L-derived cobalt-based metal organic framework and boron doping technology in electrolytic water catalysts, the problem of low catalytic efficiency caused by masking of active sites is solved, and efficient catalysis of OER reactions is achieved.

CN120158776APending Publication Date: 2025-06-17SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510519568.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-24
Publication Date
2025-06-17

AI Technical Summary

Technical Problem

The existing electrolytic water catalysts have the problem that active sites are masked and catalytic efficiency is low.

Method used

By adopting a ZIF-L-derived cobalt-based metal organic framework, more active sites are exposed using its high specific surface area two-dimensional leaf structure, and electron transport capacity is regulated through boron doping, improving the conductive properties of the catalyst and the oxidation state of the active sites.

Benefits of technology

It effectively improves the catalytic activity of the catalyst to redox reaction (OER), and improves the efficiency and performance of electrolytic oxygen analysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120158776A_ABST
    Figure CN120158776A_ABST
Patent Text Reader

Abstract

The invention discloses a ZIF-L-derived alkaline electrolysis water oxygen evolution catalyst and a preparation method and application thereof, and relates to the technical field of new energy electrolysis water catalysis, the method comprises the following steps: mixing a cobalt salt solution with a 2-methylimidazole solution to obtain a purple mixed solution; foamed nickel is put into the purple mixed solution to be aged, and a cobalt-based metal organic framework ZIF-Laton NF is obtained; adding the cobalt-based metal organic framework into a sodium borohydride solution, and carrying out ice-water bath to obtain a boron-doped cobalt-based metal organic framework B-ZIF-L (at) NF; the B-ZIF-L-X-coated NF is subjected to low-temperature annealing in an inert atmosphere, and the alkaline electrolysis water oxygen evolution catalyst B-ZIF-L-X-coated NF is obtained. The problems that in the prior art, active sites of a catalyst for electrolyzing water are masked, and the catalytic efficiency is low are solved. The change of the electron cloud distribution of the transition metal center is realized, the local electron structure is optimized, the generation of high-valence active sites is promoted, and the catalytic efficiency is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of new energy electrolytic water catalysis, and particularly relates to a ZIF-L-derived alkaline electrolytic water oxygen evolution catalyst, a preparation method thereof, and an application thereof. Background Art

[0002] Electrolysis of water includes anodic oxygen evolution reaction (OER) and cathodic hydrogen evolution reaction (HER), providing a green and sustainable energy conversion technology for hydrogen production. Compared with HER, OER is a complex four-electron reaction, involving electron-proton transfer processes of multiple intermediates, with slow reaction kinetics, which restricts the overall efficiency and energy consumption of water electrolysis. At present, OER mainly focuses on Ru (ruthenium) and Ir (iridium)-based electrocatalysts, but the high cost and scarcity of such catalysts seriously limit their large-scale commercial applications.

[0003] Researchers have explored various transition metal-based materials as alternative OER electrocatalysts, including oxides, phosphides, sulfides, borides, etc. In particular, the excellent catalytic activity of transition metal-based electrocatalytic materials in an alkaline environment and their good durability for electrochemical OER have attracted people's attention. For example, in Document 1 (Wenjie Shao, Mingjun Xiao, Chengdong Yang, et al. [J], Research Article, 2021, 18(7), 2105763.), a series of transition metal-based vanadates were synthesized for efficient OER catalysis through a simple assembly and adjustment strategy. Among them, the NiFe (nickel-iron alloy)-based catalyst with medium heterophase had an overpotential of only 267 mV at a current density of 10 mA / cm 2 and a Tafel slope of 38 mV / dec. This scheme reduces the charge transfer resistance of the catalyst by constructing a heterophase structure, promotes the charge transfer rate, and thus improves the catalytic performance of the material. However, this technology has the problem that the assembly of the heterophase structure may cause some active sites to be masked, reducing the catalytic efficiency, and the catalytic performance of the material has not been significantly improved compared with RuO2. Summary of the Invention

[0004] By providing a ZIF-L-derived alkaline electrolytic water oxygen evolution catalyst, a preparation method thereof, and an application thereof in the embodiments of this application, the problems in the prior art that the active sites of the catalyst for water electrolysis are masked and the catalytic efficiency is low are solved.

[0005] In a first aspect, an embodiment of the present application provides a method for preparing a ZIF-L-derived alkaline electrolytic water oxygen evolution catalyst, including: mixing a cobalt salt solution with a 2-methylimidazole solution to obtain a purple mixed solution; placing nickel foam in the purple mixed solution for aging to obtain a cobalt-based metal-organic framework grown on the nickel foam; adding the cobalt-based metal-organic framework to a sodium borohydride solution and performing an ice-water bath to obtain a boron-doped cobalt-based metal-organic framework; annealing the boron-doped cobalt-based metal-organic framework at a low temperature in an inert atmosphere to obtain an alkaline electrolytic water oxygen evolution catalyst.

[0006] In combination with the first aspect, in a possible implementation manner, the cobalt salt solution is any one or more of a cobalt nitrate hexahydrate solution, a cobalt nitrate tetrahydrate solution, or a cobalt chloride hexahydrate solution.

[0007] In combination with the first aspect, in a possible implementation manner, the aging temperature is 20-30 °C, and the aging time is 6-12 h.

[0008] In combination with the first aspect, in a possible implementation manner, the molar ratio of the cobalt salt solution to the 2-methylimidazole solution is 0.3-0.6:1.0-6.0.

[0009] In combination with the first aspect, in a possible implementation manner, the heating rate of the low-temperature annealing is 2-5 °C / min, the holding temperature is 300-500 °C, and the holding time is 1-4 h.

[0010] In combination with the first aspect, in a possible implementation manner, before adding the cobalt-based metal-organic framework to the sodium borohydride solution and performing an ice-water bath, it further includes: adding sodium borohydride to a dilute alkali solution and mixing evenly to obtain a mixed sodium borohydride solution.

[0011] In combination with the first aspect, in a possible implementation manner, obtaining the cobalt-based metal-organic framework grown on the nickel foam includes: washing the self-grown product on the aged nickel foam with distilled water to obtain the cobalt-based metal-organic framework.

[0012] In a second aspect, an embodiment of the present application provides a ZIF-L-derived alkaline electrolytic water oxygen evolution catalyst, which is characterized in that it is an alkaline electrolytic water oxygen evolution catalyst prepared by using the preparation method described in the first aspect or any one of the possible implementation manners of the first aspect.

[0013] In a third aspect, an embodiment of the present application provides an application of a ZIF-L-derived alkaline electrolytic water oxygen evolution catalyst in electrolytic water oxygen evolution, and uses the alkaline electrolytic water oxygen evolution catalyst prepared in the second aspect in an electrolytic water reaction.

[0014] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages: In the embodiments of the present application, by adopting a cobalt-based metal-organic framework, which is a two-dimensional leaf shape with a high specific surface area, it can increase the exposure of active sites; by doping boron into the cobalt-based metal-organic framework, the electron transport ability can be regulated, the conductivity of the catalyst can be improved, the metal d-band center can be reduced, the reaction energy barrier can be reduced, and the oxidation state of the active sites can be increased to enhance the catalytic activity for OER. It effectively solves the problem in the prior art that the active sites of the catalyst for electrolyzing water are masked and the catalytic efficiency is low. It realizes changing the electron cloud distribution of the transition metal center, optimizing its local electronic structure, promoting the generation of high-valence active sites, and thus improving the catalytic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following will briefly introduce the drawings required for the description of the embodiments of the present application or the prior art. Obviously, the drawings in the following description are some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.

[0016] Figure 1 It is a flowchart of a preparation method of a ZIF-L-derived alkaline electrolytic water oxygen evolution catalyst provided in the embodiments of the present application; Figure 2 It is an energy spectrum analysis diagram of the prepared B-ZIF-L-300@NF provided in the embodiments of the present application; Figure 3 It is a comparison diagram of X-ray diffraction results of B-ZIF-L-400@NF, B-ZIF-L-300@NF, B-ZIF-L@NF, ZIF-L@NF and ZIF-L provided in the embodiments of the present application; Figure 4a It is an example diagram of a scanning electron microscope of B-ZIF-L-300@NF provided in the embodiments of the present application; Figure 4b It is an example diagram of a scanning electron microscope of B-ZIF-L-400@NF provided in the embodiments of the present application; Figure 4c It is an example diagram of a scanning electron microscope of B-ZIF-L@NF provided in the embodiments of the present application; Figure 4d It is an example diagram of a scanning electron microscope of ZIF-L@NF provided in the embodiments of the present application; Figure 5 It is a comparison diagram of LSV curves of B-ZIF-L-400@NF, B-ZIF-L-300@NF, B-ZIF-L@NF, ZIF-L@NF and NF provided in the embodiments of the present application; Figure 6 Tafel slope diagrams of B-ZIF-L-400@NF, B-ZIF-L-300@NF, B-ZIF-L@NF, ZIF-L@NF and NF provided by embodiments of the present application; Figure 7 Cyclic voltammetry durability test diagram of B-ZIF-L-300@NF provided by embodiments of the present application. Detailed implementation manners

[0017] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0018] Some technologies related to the embodiments of the present application are described below to facilitate understanding. It should be considered that they are only exemplary. Therefore, those of ordinary skill in the art should recognize that various changes and modifications can be made to the embodiments described here without departing from the scope and spirit of the present application. Similarly, for the sake of clarity and conciseness, some descriptions of well-known functions and structures are omitted in the following description.

[0019] Figure 1 is a flowchart of a method for preparing a ZIF-L-derived alkaline electrolytic water oxygen evolution catalyst provided by an embodiment of the present application, including steps 101 to 104. Among them, Figure 1 This is only an execution order shown in the embodiment of the present application, and does not represent the only execution order of a method for preparing a ZIF-L-derived alkaline electrolytic water oxygen evolution catalyst. Under the condition that the final result can be achieved, Figure 1 the steps shown can be executed in parallel or reversed.

[0020] Step 101: Mix a cobalt salt solution and a 2-methylimidazole solution to obtain a purple mixed solution. In the embodiment of the present application, the cobalt salt solution and the 2-methylimidazole solution are respectively magnetically stirred, and then the 2-methylimidazole solution is quickly poured into the cobalt salt solution and stirred to obtain a purple mixed solution. Among them, the molar ratio of the cobalt salt solution to the 2-methylimidazole solution is 0.3-0.6:1.0-6.0. Exemplarily, the molar ratio of the cobalt salt solution to the 2-methylimidazole solution can be 1:2, 1:4 or 1:8. In a preferred embodiment, the molar ratio of the cobalt salt solution to the 2-methylimidazole solution is 1:8. Exemplarily, the molar concentration of the cobalt salt solution is 0.05M / L, and the molar concentration of the 2-methylimidazole solution is 0.1M / L, 0.2M / L, 0.4M / L or 0.6M / L.

[0021] Specifically, the cobalt salt solution and 2-methylimidazole solution of the present application are prepared by mixing cobalt salt and 2-methylimidazole with deionized water respectively. The cobalt salt solution is any one or a mixture of several of cobalt nitrate hexahydrate solution, cobalt nitrate tetrahydrate solution or cobalt chloride hexahydrate solution.

[0022] Step 102: Put nickel foam into the purple mixed solution for aging to obtain cobalt-based metal-organic framework grown on the nickel foam. In the embodiment of the present application, the nickel foam is put into the uniformly mixed solution for aging, the aging temperature is 20-30 °C, and the aging time is 6-12 h. Then, the product grown on the nickel foam after aging is washed with distilled water to obtain an integrated material coated with nickel foam, that is, cobalt-based metal-organic framework.

[0023] In the embodiment of the present application, the nickel foam is pretreated before being put into the purple mixed solution, specifically as follows: The nickel foam is soaked in 1 mol / L dilute hydrochloric acid and ultrasonically treated for 10 min to remove the oxide layer, impurities, etc. on its surface. Then it is ultrasonically treated with ethanol for 10 min to remove organic impurities, hydrochloric acid residues and other impurities on the surface of the nickel foam. Then the nickel foam is washed with deionized water to further remove ethanol residues or other water-soluble impurities on the surface of the nickel foam. Finally, it is dried in a vacuum drying oven at 60 °C to avoid oxidation of the nickel foam during the drying process, or changes in the structure or performance of the nickel foam at high temperature, and clean and dry nickel foam is obtained and put into the purple mixed solution.

[0024] By loading a two-dimensional leaf-shaped cobalt-based metal-organic framework with a high specific surface area on the nickel foam, the present application helps to expose more active sites and improve the catalytic efficiency. And compared with the poor electron transport ability of traditional MOF (metal-organic framework), the sheet-like cobalt-based metal-organic framework can provide a shorter electron transport path due to its highly planar structure, thus improving the conductivity.

[0025] Step 103: Add the cobalt-based metal-organic framework into the sodium borohydride solution and perform an ice-water bath to obtain boron-doped cobalt-based metal-organic framework. In the embodiment of the present application, sodium borohydride is added to the dilute alkali solution and mixed evenly to obtain the mixed sodium borohydride solution. Exemplarily, the dilute alkali solution is a sodium hydroxide solution with a pH of 9-10. The cobalt-based metal-organic framework is added to the sodium borohydride solution after mixing sodium borohydride and sodium hydroxide solution for an ice-water bath to obtain boron-doped cobalt-based metal-organic framework.

[0026] Specifically, the reduction reaction of sodium borohydride is relatively intense at room temperature, releasing a large amount of hydrogen. During the escape process of hydrogen bubbles, the cobalt-based metal-organic framework grown on the surface of nickel foam will be impacted, resulting in the dropping of a large amount of metal-organic framework. In this application, an ice-water bath is used to make the reaction occur more mildly, reduce the bubble escape rate, and slow down the impact on the cobalt-based metal-organic framework.

[0027] Sodium borohydride will rapidly decompose and release hydrogen in acidic or neutral aqueous solutions to form a metal salt solution. To inhibit the hydrolysis of sodium borohydride, it is necessary to maintain it under weak alkaline conditions (exemplarily, the pH value is 8-10) to improve the stability of sodium borohydride. The specific operation is as follows: Prepare a 0.1-0.5M NaOH solution, add NaBH4 while stirring, and control the final solution concentration according to experimental requirements. In this application, the final concentration of the NaBH4 solution is 0.1M / L. The specific operation is to place 20 mL of 0.2M NaOH solution in an ice-water bath, and then add 0.07566 g of NaBH4, and stir until completely dissolved.

[0028] This application utilizes the formation of strong metal-boron bonds between boron doping and transition metals to change the electron cloud distribution of the transition metal center, optimize its local electronic structure, and promote the generation of high-valence active sites.

[0029] Step 104: Anneal the boron-doped cobalt-based metal-organic framework in an inert atmosphere at a low temperature to obtain an alkaline electrolytic water oxygen evolution catalyst. In the embodiments of this application, the inert atmosphere can be an inert gas space such as argon or helium. Exemplarily, argon is used in this application. Place the boron-doped cobalt-based metal-organic framework in a tubular furnace with an argon atmosphere, heat it at a heating rate of 2-5 °C / min to 300-500 °C, and keep it at this temperature for 1-4 h to obtain an alkaline electrolytic water oxygen evolution catalyst. The low-temperature annealing adopted in this application can better maintain the original morphology of the cobalt-based metal-organic framework.

[0030] To prove the composition and effect of the alkaline electrolytic water oxygen evolution catalyst, three examples and two comparative examples were carried out in this application, as follows.

[0031] Example 1: First, 0.58 g of cobalt nitrate hexahydrate and 1.31 g of 2-methylimidazole were respectively dissolved in 40 mL of deionized water at room temperature. After magnetic stirring for 5 min, the 2-methylimidazole solution was quickly poured into the cobalt nitrate hexahydrate solution and stirred for another 5 min to obtain a uniformly mixed purple solution. Finally, the treated nickel foam was placed into the purple mixed solution and aged at 25 °C for 12 h to obtain a cobalt-based metal-organic framework grown on the nickel foam, abbreviated as ZIF-L@NF. The obtained cobalt-based metal-organic framework ZIF-L@NF was added to a solution of 20 mL of a mixture of sodium borohydride solution and sodium hydroxide solution with a molar concentration of 0.1 mol / L and subjected to an ice-water bath to obtain a boron-doped cobalt-based metal-organic framework, abbreviated as B-ZIF-L@NF.

[0032] To prove the composition of the alkaline electrolytic water oxygen evolution catalyst (B-ZIF-L@NF), XRD (X-ray diffraction) tests were carried out. The test results are as Figure 3 shown. To prove the microscopic morphology of the alkaline electrolytic water oxygen evolution catalyst (B-ZIF-L@NF), SEM (scanning electron microscopy) tests were carried out. The test results are as Figure 4a shown, and the microscopic morphology of the alkaline electrolytic water oxygen evolution catalyst (B-ZIF-L@NF) is a two-dimensional leaf-like structure.

[0033] To prove the electrochemical performance of the alkaline electrolytic water oxygen evolution catalyst (B-ZIF-L@NF), electrochemical performance tests were carried out. The specific method of the electrochemical performance test was to carry out the electrochemical performance test under a three-electrode system composed of the material to be tested (alkaline electrolytic water oxygen evolution catalyst, B-ZIF-L@NF) as the working electrode, a mercury oxide electrode as the reference electrode, a graphite rod electrode as the counter electrode, and 1 M KOH solution as the electrolyte. The test results are as Figure 5 shown, where Current Density represents the current density and Potential represents the potential. In the voltage range of 1 - 1.8 V, when the current density is 10 mA·m -2 , the overpotential is 168 mV, and when the current density is 200 mA·cm -2 , the overpotential is 376 mV.

[0034] The Tafel slope was calculated through current polarization tests (an important parameter in the electrochemistry field to evaluate the electrode reaction kinetics, reflecting the logarithmic relationship between the current density and the overpotential, and used to characterize the electrode reaction rate and mechanism). The test results are as Figure 6 shown, and the Tafel slope of the alkaline electrolytic water oxygen evolution catalyst (B-ZIF-L@NF) is 103.4 mV dec -1 .

[0035] Example 2: First, 0.58 g of cobalt nitrate hexahydrate and 1.31 g of 2-methylimidazole were separately dissolved in 40 mL of deionized water at room temperature. After magnetic stirring for 5 min, the 2-methylimidazole solution was quickly poured into the cobalt nitrate hexahydrate solution and stirred for another 5 min to obtain a uniformly mixed purple solution. Finally, the treated nickel foam was placed into the purple solution and aged at 25 °C for 12 h to obtain a cobalt-based metal-organic framework grown on nickel foam, abbreviated as ZIF-L@NF. The obtained cobalt-based metal-organic framework ZIF-L@NF was added to a solution of 20 mL of a mixture of sodium borohydride solution and sodium hydroxide solution with a molar concentration of 0.1 mol / L for an ice-water bath to obtain a boron-doped cobalt-based metal-organic framework, abbreviated as B-ZIF-L@NF. B-ZIF-L@NF was placed in a tubular furnace under an argon atmosphere and heated to 300 °C at a rate of 2 °C / min and held for 2 h to successfully prepare an alkaline electrolytic water oxygen evolution catalyst, named B-ZIF-L-300@NF.

[0036] To prove the composition of the alkaline electrolytic water oxygen evolution catalyst (B-ZIF-L-300@NF), EDS (Energy Dispersive Spectroscopy) tests were carried out. The test results are as Figure 2 shown, where B represents boron, C represents carbon, N represents nitrogen, and Co represents cobalt. To prove the structure and microscopic morphology of the alkaline electrolytic water oxygen evolution catalyst (B-ZIF-L-300@NF), XRD (X-ray diffraction) and SEM (scanning electron microscope) tests were carried out. The test results are as Figure 3 and Figure 4b shown, where Intensity represents light intensity, Degree represents angle, and ZIF-L (CCDC: 1509273) is the PDF card corresponding to the XRD of this material in the Cambridge Crystallographic Database. The microscopic morphology of the alkaline electrolytic water oxygen evolution catalyst (B-ZIF-L-300@NF) still maintains a two-dimensional blade-like structure, and the surface roughness increases compared to the cobalt-based metal-organic framework (ZIF-L@NF).

[0037] To prove the electrochemical performance of the alkaline electrolytic water oxygen evolution catalyst (B-ZIF-L-300@NF), electrochemical performance tests were carried out. The specific method for the electrochemical performance test was to conduct electrochemical performance tests under a three-electrode system composed of the material to be tested (alkaline electrolytic water oxygen evolution catalyst, B-ZIF-L-300@NF) as the working electrode, a mercury oxide electrode as the reference electrode, a graphite rod electrode as the counter electrode, and 1 M KOH solution as the electrolyte. The test results are as Figure 5As shown, where Current Density represents current density and Potential represents electric potential. In the voltage range of 1 - 1.8V, when the current density is 10mA·m -2 , the overpotential is 220mV, and when the current density is 200mA·cm -2 , the overpotential is 330mV.

[0038] The Tafel slope was calculated through current polarization tests (an important parameter in the field of electrochemistry for evaluating the kinetics of electrode reactions, reflecting the logarithmic relationship between current density and overpotential, and used to characterize the rate and mechanism of electrode reactions). The test results are as Figure 6 shown. The Tafel slope of the alkaline electrolytic water oxygen evolution catalyst (B-ZIF-L-300@NF) is 78.6mV dec -1 .

[0039] Through 1500 cycles of CV durability tests, the test results are as Figure 7 shown. When the current density is 200mA·cm -2 , the overpotential only increases by 10% - 12%.

[0040] Example 3: First, 0.58g of cobalt nitrate hexahydrate and 1.31g of 2-methylimidazole were respectively dissolved in 40mL of deionized water at room temperature. After magnetic stirring for 5min, the 2-methylimidazole solution was quickly poured into the cobalt nitrate hexahydrate solution and stirred for another 5min to obtain a uniformly mixed purple solution. Finally, the treated nickel foam was placed into the purple mixed solution and aged at 25°C for 12h to obtain a cobalt-based metal-organic framework grown on nickel foam, simply referred to as ZIF-L@NF. The obtained cobalt-based metal-organic framework ZIF-L@NF was added to a mixed solution of 20mL of sodium borohydride solution and sodium hydroxide with a molar concentration of 0.1mol / L for an ice-water bath to obtain a boron-doped cobalt-based metal-organic framework, simply referred to as B-ZIF-L@NF. The boron-doped cobalt-based metal-organic framework was placed in a tubular furnace under an argon atmosphere, heated to 400°C at a rate of 2°C / min and held for 2h to successfully prepare an alkaline electrolytic water oxygen evolution catalyst, named B-ZIF-L-400@NF.

[0041] To prove the composition of the alkaline electrolytic water oxygen evolution catalyst (B-ZIF-L-400@NF), XRD (X-ray diffraction) tests were carried out. The test results are as Figure 3 shown. To prove the microscopic morphology of the alkaline electrolytic water oxygen evolution catalyst (B-ZIF-L-400@NF), SEM (scanning electron microscopy) tests were carried out. The test results are as Figure 4cAs shown, the microscopic morphology of the alkaline electrolytic water oxygen evolution catalyst (B-ZIF-L-400@NF) is a two-dimensional leaf-like structure.

[0042] To prove the electrochemical performance of the alkaline electrolytic water oxygen evolution catalyst (B-ZIF-L-400@NF), an electrochemical performance test was carried out. The specific method of the electrochemical performance test was to conduct the electrochemical performance test under a three-electrode system composed of the material to be tested (alkaline electrolytic water oxygen evolution catalyst, B-ZIF-L-400@NF) as the working electrode, a mercury oxide electrode as the reference electrode, a graphite rod electrode as the counter electrode, and 1 M KOH solution as the electrolyte. The test results are as Figure 5 shown. In the voltage range of 1 - 1.8 V, when the current density is 10 mA·cm -2 , the overpotential is 200 mV, and when the current density is 200 mA·cm -2 , the overpotential is 399 mV.

[0043] The Tafel slope was calculated through a current polarization test. The test results are as Figure 6 shown. The Tafel slope of the alkaline electrolytic water oxygen evolution catalyst (B-ZIF-L-400@NF) is 109.6 mV·dec -1 .

[0044] Comparative Example 1: According to the methods of the above two examples, a cobalt-based metal-organic framework was obtained, abbreviated as ZIF-L@NF. XRD testing was carried out on the cobalt-based metal-organic framework. The test results are as Figure 3 shown, and only the characteristic peaks of ZIF-L@NF exist. To observe the microscopic morphology of the cobalt-based metal-organic framework, SEM testing was carried out. The test results are as Figure 4c shown. The microscopic morphology of the cobalt-based metal-organic framework is a two-dimensional leaf-like structure.

[0045] To prove the electrochemical performance of the cobalt-based metal-organic framework, an electrochemical performance test was carried out. The specific method of the electrochemical performance test was to conduct the electrochemical performance test under a three-electrode system composed of the material to be tested (cobalt-based metal-organic framework) as the working electrode, a mercury oxide electrode as the reference electrode, a graphite rod electrode as the counter electrode, and 1 M KOH solution as the electrolyte. The test results are as Figure 5 shown. In the voltage range of 1 - 1.8 V, when the current density is 10 mA·cm -2 , the overpotential is 316 mV, and when the current density is 200 mA·cm -2 , the overpotential is 532 mV.

[0046] The Tafel slope was calculated through a current polarization test. The test results are as Figure 6 shown. The Tafel slope of ZIF-L@NF is 128.4 mV·dec-1 .

[0047] By comparing Example 1 with Comparative Example 1, it can be seen that the introduction of boron into ZIF-L@NF can not only change the electron cloud distribution of the transition metal center and promote the formation of high-valent active sites, but also change the electronic structure of the catalyst, improve the conductivity of the catalyst, and increase the electrochemical oxygen evolution performance.

[0048] Comparative Example 2: The test was conducted using nickel foam as the working electrode, referred to as NF. The specific method of the electrochemical performance test is to conduct the electrochemical performance test in a three-electrode system consisting of the material to be tested (nickel foam) as the working electrode, the mercuric oxide electrode as the reference electrode, the graphite rod electrode as the counter electrode, and 1M KOH solution as the electrolyte. The test results are as follows Figure 5 As shown, in the voltage range of 1-1.8 V, the current density is 10 mA cm -2 When the overpotential is 354 mV, the current density is 200 mA cm -2 When , the overpotential is 560mV.

[0049] The Tafel slope is calculated by current polarization test. The test results are as follows Figure 6 As shown, the Tafel slope of nickel foam is 131.9 mV·dec -1 .

[0050] By comparing the LSV (linear sweep voltammetry) curves, Tafel slope graphs and SEM (scanning electron microscope) graphs of the examples and the comparative examples, it is found that the catalytic performance of the boron-doped cobalt-based metal organic framework after boron treatment and low-temperature annealing has been greatly improved. However, compared with B-ZIF-L-300@NF, the performance of B-ZIF-L-400@NF has shown a downward trend. This is because the annealing temperature is too high, causing the ZIF-L (metal organic framework) to collapse during the annealing process, resulting in a reduction in active sites on the surface of the material. The Tafel slope curve can reflect the difference in electrocatalytic kinetic performance, that is, the smaller the value of the overpotential increase when the current density increases tenfold, the more it can explain that the catalyst B-ZIF-L-300@NF has good catalytic performance.

[0051] Although the present application provides method operation steps such as embodiments or flow charts, more or fewer operation steps may be included based on routine or non-creative work. The order of steps listed in this embodiment is only one way of executing the steps among many, and does not represent the only execution order.

[0052] The embodiments of the present application also provide a ZIF-L-derived alkaline water electrolysis oxygen evolution catalyst, and the alkaline water electrolysis oxygen evolution catalyst is prepared by the method of the embodiments of the present application.

[0053] The embodiment of the present application also provides an application of a ZIF-L-derived alkaline electrolytic water oxygen evolution catalyst in electrolytic water oxygen evolution.

[0054] The above embodiments are only used to illustrate the technical solutions of the present application, rather than limiting the present application; although the present application has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the present application.

Claims

1. A method for preparing a ZIF-L derived alkaline water electrolysis oxygen evolution catalyst, characterized in that: include: The cobalt salt solution and the 2-methylimidazole solution are mixed to obtain a purple mixed solution; Adding nickel foam into the purple mixed solution for aging to obtain a cobalt-based metal organic framework grown on the nickel foam; Adding the cobalt-based metal organic framework into a sodium borohydride solution and subjecting the solution to an ice-water bath to obtain a boron-doped cobalt-based metal organic framework; The boron-doped cobalt-based metal organic framework is subjected to low-temperature annealing in an inert atmosphere to obtain an alkaline water electrolysis oxygen evolution catalyst.

2. The method according to claim 1, characterized in that The cobalt salt solution is any one or more of a hexahydrate cobalt nitrate solution, a tetrahydrate cobalt nitrate solution or a hexahydrate cobalt chloride solution.

3. The method according to claim 1, characterized in that The aging temperature is 20-30° C., and the aging time is 6-12 hours.

4. The method according to claim 1, characterized in that The molar ratio of the cobalt salt solution to the 2-methylimidazole solution is 0.3-0.6:1.0-6.

0.

5. The method according to claim 1, characterized in that The low-temperature annealing has a heating rate of 2-5°C / min, a holding temperature of 300-500°C, and a holding time of 1-4h.

6. The method according to claim 1, characterized in that Before adding the cobalt-based metal organic framework into the sodium borohydride solution and performing ice water bath, the method further comprises: Sodium borohydride is added into the dilute alkali solution and mixed evenly to obtain a mixed sodium borohydride solution.

7. The method according to claim 1, characterized in that The method of obtaining a cobalt-based metal organic framework grown on nickel foam comprises: The self-grown product on the aged nickel foam is washed with distilled water to obtain the cobalt-based metal organic framework.

8. A ZIF-L derived alkaline water electrolysis oxygen evolution catalyst, characterized in that: An alkaline water electrolysis oxygen evolution catalyst prepared by the preparation method according to any one of claims 1 to 7.

9. Use of a ZIF-L derived alkaline water electrolysis oxygen evolution catalyst as claimed in claim 8 in water electrolysis oxygen evolution.